PEMIKIRAN EKONOMI ISLAM TENTANG UANG, HARGA DAN PASAR - Iqbal, Ichsan (The Pontianak State Institute of Islamic Studies, 2012)
ABSTRACT The making of coins is a guarantee given by the authorities that a coin contains an amount of specific gold and silver content. The manufacture is a religious office, and therefore not subject to temporal rules. And money is used for legal tender, measurement of prices, assets and deposits in banks. Money is not the means to speculate. A fair price is the price at which people sell goods and generally accept as the equivalent of the goods sold in a certain place and at a certain time. The market is the meeting place between demand and supply in order to determine the price. The price depends not only on the supply, but also relies on the strength of demand. Therefore, the increase or decrease in prices are not always related to the decrease or increase in production.